Limitations to growth: Social-ecological challenges to aquaculture development in five wealthy nations - Young, Nathan; Brattland, Camilla; Digiovanni, Celeste; Hersoug, Bjørn; Johnsen, Jahn Petter; Karlsen, Kine Mari; Kvalvik, Ingrid; Olofsson, Erik; Simonsen, Knud; Solås, Ann-Magnhild; Thorarensen, Helgi (Marine Policy, 2019)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Published version available at https://doi.org/10.1016/j.marpol.2019.02.022. Aquaculture is a major contributor to global food production, but has attracted considerable controversy. Disagreements over the social and ecological impacts of aquaculture (positive and negative) have hindered further expansion of aquaculture production, particularly in wealthy democratic countries. This article presents findings from a series of workshops bringing international aquaculture scholars together from the natural and social sciences to examine and compare social-ecological challenges facing aquaculture development in five nations: Canada, the Faroe Islands, Iceland, Norway, and Sweden. This multinational comparison provides unique insights into common and particular challenges in aquaculture governance – a dimension that is missing in current literature about the industry. A political ecology framework from the environmental social sciences is used to examine how natural and human phenomena interact to shape these challenges and frame the conflicts that often result. The analysis reveals a wide range of social-ecological factors limiting aquaculture expansion in the five countries, including access to suitable environments, interactions with other sectors, and policy and regulatory gaps – not only with respect to aquaculture, but also on related issues such as marine spatial planning and the involvement of indigenous peoples in decision-making. The findings provide preliminary guidance for future policy development and comparative aquaculture research.